INFORMATION TECHNOLOGY SYSTEMS FOR INTERORGANIZATIONAL CONNECTITIVY DOI:10.5585/rai.v6i2.377 (INMR - Innovation & Management Review, 2009)
A coordinated effort among constituents in a supply chain may eliminate inefficiencies and generate significant savings for each member. The connectivity between information technology systems of distinct firms can contribute to a better coordination and integration of the supply chain. The implementation of connectivity technologies is not an easy task, though, because it involves significant sums of capital and the resulting benefits are not always clear to their constituents. Hence, many enterprises hesitate to adopt IT inter-organizational connecting systems and some of them will do only under partners´ imposition. To examine this context, this exploratory research, a case study, targets at analyzing the technology status of connectivity in a firm that uses connecting IT systems, where operating standards were established by the commercial partners. This study was undertaken in an auto parts company and showed the main problems, the operating difficulties and how the connectivity technology is perceived in the company, which was induced to adopt inter-organizational connection technology.